COMPARATIVE ANALYSIS OF MAJOR JOINT INJURIES OF VARIOUS ROAD TRAFFIC ACCIDENT PARTICIPANTS - Zaynitdin A. Giyasov; Dilshod E.Gulyamov (Central Asian Journal of Medicine, 2025)
An analysis of forensic medical examination materials was conducted in cases of injuries to large joints in traffic accidents. In 77.0% of cases, isolated joint injuries were present, more often in the lower extremities. Combined injuries to the joints of the upper limbs, more often to the left, were characteristic of car drivers, and combined injuries to the lower limbs were mainly observed in pedestrians. Cut wounds of the periarticular soft tissues were found only in drivers, while isolated dislocations were found in pedestrians. Ruptures and sprains of ligaments were mainly observed in pedestrians and car passengers. The features of the localization and nature of injuries to large joints can be used as an auxiliary feature for differentiating the status of road traffic accident participants.